The manifestation of participation within a co‐design process involving patients, significant others and health‐care professionals - Sebastian Lindblom; Maria Flink; Marie Elf; Ann Charlotte Laska; Lena von Koch; Charlotte Ytterberg (Wiley, 2021)
Abstract Background Despite intentions to increase user participation in the development of health services, the concept of participation and how it unfolds within studies with a participatory design has rarely been addressed. Objective The aim of this study was to describe how user participation manifests itself within a co‐design process involving patients, significant others and health‐care professionals, including potential enablers or barriers. Methods This study was conducted in the context of a co‐design process of a new person‐centred transition from a hospital to continued rehabilitation in the home involving three patients with stroke, one significant other and 11 professionals. Data were collected by observations during the workshops, semi‐structured interviews and questionnaires. Results Four categories: 'Composition of individuals for an adaptive climate'; 'The balancing of roles and power'; 'Different perspectives as common ground for a shared understanding'; and 'Facilitating an unpredictable and ever‐adaptive process', with all together nine subcategories, resulted from the analysis. Participation varied between individuals, groups and steps within the process, and on the topic of discussions and the motivation to contribute. Discussion/Conclusion Participation is not something that is realized by only applying participatory design methodology. Participation manifests itself through the interaction of the participants and their skills to handle different perspectives, roles and assignments. Participation is enabled by individual, group and facilitating aspects. Co‐design processes should allow for varying levels of participation among the participants and throughout the process. Patient or public contribution Patients, significant others and health‐care professionals participated as co‐designers of a care transition model between hospital and home.